The prevalence of orofacial clefts in Qatar : a cross-sectional nationwide study - Mohannad Nawaf Khandakji; Mohammed Hammamy; Mariam Albaloushi; Najat Alhashimi (BMC, 2024)
Abstract Background Cleft lip and palate are congenital craniofacial anomalies that significantly impact individuals and their families, both medically and psychosocially. The Qatari population has unique characteristics that are suggestive of a high prevalence of congenital anomalies: high consanguinity rate, large family size, advanced paternal age and high prevalence of certain genetic disorders. The lack of existing data concerning the epidemiology of cleft lip and/or palate in Qatar warrants a descriptive study addressing this topic. Methods A retrospective nationwide hospital-based cross-sectional study conducted to determine the prevalence of orofacial clefts in Qatar from 2016 to 2021. Data were extracted from the corporation's Cerner database and electronic health records. Information concerning the cleft's characteristics, type, affected side, patient's gender, presence of associated syndromes, nationality, and maternal age were collected. Results Out of the 147,727 live births, 148 had an orofacial cleft. The prevalence of cleft lip and/or palate was determined to be 1 per 1000 livebirths (95% CI: 0.85, 1.18). The prevalence of cleft lip was 0.18 (95% CI: 0.12, 0.27), cleft palate 0.39 (95% CI: 0.30, 0.51), and cleft lip and palate 0.43 (95% CI: 0.33, 0.55). Qataris had a prevalence of CL 0.25, CP 0.40, and CLP 0.56, compared to 0.16, 0.39, 0.39 for non-Qataris (p-value 0.186). Unilateral clefts predominated over bilateral (74.4% and 25.6%, respectively). Among the unilateral cases, 70.2% occurred on the left side. Most cases were isolated clefts, with only 10.2% having associated syndromes. Conclusions The prevalence of orofacial clefts in Qatar is consistent with the globally reported prevalence. Most cases were unilateral and on the left side. Associated syndromes were infrequent and more common with cleft palate alone. Intriguing patterns were revealed between Qatari nationals and non-Qatari residents, with specific subtypes of orofacial clefts showing higher prevalence among nationals.